Asymmetrical Barkhausen Noise of a Hard Milled Surface - Čilliková, Mária (Materials (Basel), 2021)
This study is focused on the asymmetrical Barkhausen noise emission of a hard milled surface during cyclic magnetisation. The Barkhausen noise is studied as a function of the magnetising voltage and the hard milled surface is compared with a surface after heat treatment. The asymmetry in the Barkhausen noise emission after hard milling occurs due to the typical “sandwich” structure and the different magnetic hardnesses of the different layers beneath the free surface. Furthermore, this asymmetry is also due to the preferential orientation of the matrix in the direction of the cutting speed and magnetostatic fields, which hinder or favour the premagnetising process.